Design and validation of a psychosocial well-being scale (BPS) for high school students - José Manuel Solís-Miranda; Eduardo Hernández Padilla (Revista de Psicología y Ciencias del Comportamiento de la Unidad Académica de Ciencias Jurídicas y Sociales)
The objective was to design and validate a psycho-social well-being scale for a secondary school po-pulation. A total of 514 adolescents between 11 and 16 years of age (248 males/266 females) participa-ted. The scale started with 15 items organized in 3 dimensions, and was submitted to content valida-tion where it was increased to 23 items. Explora-tory Factor Analysis (KMO=.909 and Bartlett's significance level<.001) and Confirmatory Factor Analysis (three-factor model of 22 items withgoodness-of-fit indices: χ2/d.f.=1.795; RMSEA=.056; CFI=.883; TLI=.867) were performed. The RASCH modeling visualizes the range of measures between values 7 and 1.3, a mean of 100 and standard deviation of 15, correct fit indices (infit=.82 and oufit=1.20) and range of respondent abilities between 60 and 160 points. This is an exploration of an instrument to assess psychosocial well-being in high school students according to Isaac Prilleltensky's theoretical proposal.